2015
DOI: 10.1590/2176-9451.20.3.101-108.bbo
|View full text |Cite
|
Sign up to set email alerts
|

Treating dental crowding with mandibular incisor extraction in an Angle Class I patient

Abstract: Mandibular dental crowding often encourages patients to seek orthodontic treatment. The orthodontist should decide between protrusion of incisors or decrease in dental volume so as to achieve proper alignment and leveling. The present study reports the treatment of an Angle Class I malocclusion adolescent female brachyfacial patient with severe mandibular dental crowding, increased curve of Spee and deep overbite. The patient was treated with extraction of a mandibular incisor. This case was presented to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It normally happens in non-extraction cases, leading the soft tissue to move forward. 15 From this case report, it can be concluded that the treatment goal has been achieved to treat the malocclusion with impacted canine. The impacted canine could be retracted with gold chain combined with MBT orthodontic prescription into its physiological position and the patient was satisfied with the aesthetic result and stomatognathic function.…”
Section: Discussionmentioning
confidence: 88%
“…It normally happens in non-extraction cases, leading the soft tissue to move forward. 15 From this case report, it can be concluded that the treatment goal has been achieved to treat the malocclusion with impacted canine. The impacted canine could be retracted with gold chain combined with MBT orthodontic prescription into its physiological position and the patient was satisfied with the aesthetic result and stomatognathic function.…”
Section: Discussionmentioning
confidence: 88%
“…The minor change caused to mandibular intercanine width can be considered a factor that contributed to increased long-term alignment stability. (5) It is well-known that a Class I canine relationship is important for functional occlusion. In this situation, a canine-protected occlusion became a premolar-protected occlusion during the mandibular lateral or working excursions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Among all the factors contributing to oral-facial esthetics, dental crowding is considered an important issue, encouraging people to seek orthodontic treatment. 5 Dental crowding is a term used to illustrate the presence of dental irregularity or insufficiency of space within the dental arcade; 6 crowding with a discrepancy of greater than 3 mm is considered significant enough to warrant treatment. 7 Theories regarding the etiology of dental crowding are divergent and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4 Among all the factors contributing to oral-facial esthetics, dental crowding is considered an important issue, encouraging people to seek orthodontic treatment. 5…”
Section: Introductionmentioning
confidence: 99%